1984
DOI: 10.1080/00223980.1984.9923670
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Tension and Closeness to Others: Stress and Interpersonal Distance Preference

Abstract: The prediction that increased tension would lead to a preference for greater distance from others was tested on 40 male and 40 female Ss approached in eight natural settings of high or low tension and their distance preference measured. Ss in the four higher-tension situations indicated a preference for significantly more distance. Self-reported tension was correlated significantly and positively with the distance preferred across all eight situations. There was no effect of sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Social ties can be a source of stress, especially in close relationships (Belle, 1982;Bolger, DeLongis, Kessler, & Schilling, 1989;Bruhn & Phillips, 1984;McGonagle & Kessler, 1990;Rook, 1984Rook, , 1990. Individuals differ in their tolerance of proximity and the number of persons around them (Burgess, 1983;Insel & Lindgren, 1978;Long, 1984;Salzinger, 1982). Warheit et al (1982) found that among various racial and ethnic groups, the use of familial and friendship networks did not appear to ameliorate mental health symptoms.…”
mentioning
confidence: 95%
“…Social ties can be a source of stress, especially in close relationships (Belle, 1982;Bolger, DeLongis, Kessler, & Schilling, 1989;Bruhn & Phillips, 1984;McGonagle & Kessler, 1990;Rook, 1984Rook, , 1990. Individuals differ in their tolerance of proximity and the number of persons around them (Burgess, 1983;Insel & Lindgren, 1978;Long, 1984;Salzinger, 1982). Warheit et al (1982) found that among various racial and ethnic groups, the use of familial and friendship networks did not appear to ameliorate mental health symptoms.…”
mentioning
confidence: 95%
“…Withingroup interactions also take place in closer IDs than between-group interactions (Novelli, Drury, and Reicher, 2010). Other factors that may affect IDP include stress (Dosey and Meisels, 1969;Hayduk, 1983;Long, 1984), status (Gifford, 1982), size of the room and height of the ceiling (Madanipour, 2003), outdoor or indoor environment (Cochran, Hale and Hissam 1984), clothing (Workman, 1987), attachment style (Bar-Haim, Aveizer, Berson and Sagi, 2002), and social stigma (Madanipour, 2003).…”
mentioning
confidence: 99%
“…The previous studies showed that there were many variables that had an influence on interpersonal distance, such as density (Kaya & Erkíp, 1999;Rüsteml, 1992;Sinha & Mukherjee, 1996), heat and noise (Bell & Barnard, 1984), culture (e.g., Barry, 2002;Beaulieu, 2004;Huff, 2001;Li, 2001), sex (Baxter, 1970;Evans & Howard, 1973;Fisher & Byrne, 1975;Gifford, 1982), attraction (Allgeier & Byrne, 1973;Michinov & Monteil, 2002), relationship (Aiello & Cooper, 1972), age (Naus & Eckenrode, 1974;Webb & Weber, 2003), mood states (Long, 1984;Yamaguchi & Suzuki, 1996), personality (Kaitz, Bar-Haim, Lehrer, & Grossman, 2004;Ray, 1984), etc.…”
mentioning
confidence: 99%